Epilepsy Surgery in Children and Adolescents - Ramantani, Georgia; Zentner, Josef (Neurology International Open, 2017)
Epilepsy surgery has been established in recent years as an effective treatment option for children and adolescents with pharmacoresistant structural epilepsies. Thanks to advances in neurosurgery, anesthesia and intensive care, epilepsy surgery is also possible in infants with excellent results. Epilepsy surgery should be considered in children with structural epilepsies and presurgical evaluation should be initiated at the latest when the criteria for pharmacoresistance are met. Focal cortical dysplasia and glioneuronal tumors are the most common etiologies in pediatric cohorts. Postoperative seizure-freedom depends on completeness of resection. In childhood, multilobular and hemispheric interventions predominate, whereas adults commonly undergo temporal resections. The extent of resections decreases with age. Younger children often require larger resections, but have higher capacities to compensate for neurological deficits, due to functional plasticity. Postoperative seizure freedom depends on the epilepsy syndrome, underlying etiology and accurate demarcation of the epileptogenic zone. Postoperatively, two-thirds of the children remain seizure-free in the long-term. Significant improvements in cognitive development are observed with seizure control. In addition to the development of non-invasive methods for presurgical evaluation, it is crucial to reduce the latency between the establishment of pharmacoresistance, presurgical evaluation and surgical treatment in suitable candidates. Multicentric studies with longer observation intervals are urgently needed in order to identify predictors of seizure freedom and favorable developmental trajectories, to facilitate the selection of optimal candidates and to improve counseling of patients and their families.
Keywords: epilepsy surgery; pharmacoresistance; development; focal cortical dysplasia; glioneuronal tumor